2015
DOI: 10.1111/iwj.12412
|View full text |Cite
|
Sign up to set email alerts
|

Ozonated saline shows activity against planktonic and biofilm growing Staphylococcus aureus in vitro: a potential irrigant for infected wounds

Abstract: Infections associated with deep wounds require extensive surgical and medical care. New adjunctive treatments are required to aid in the eradication of the bacterial biofilms found on infected wounds and, in particular, any underlying hardware. Ozone has been used as a safe and efficient disinfectant in water treatment plants for many years. The purpose of this study is to investigate the anti-biofilm potential of ozonated saline against biofilms of Staphylococcus aureus, a microorganism commonly implicated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 25 publications
0
14
0
2
Order By: Relevance
“…The exact positive effect mechanism of ozone has not yet been established but is probably due to the increased circulation of blood that delivers increased O 2 to damaged tissues. This process increases general metabolism, boosts cellulary antioxidant enzyme capacity, activates the immune system and promotes the release of growth factors from platelets 5,6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…The exact positive effect mechanism of ozone has not yet been established but is probably due to the increased circulation of blood that delivers increased O 2 to damaged tissues. This process increases general metabolism, boosts cellulary antioxidant enzyme capacity, activates the immune system and promotes the release of growth factors from platelets 5,6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…It also seems to show superior results in the treatment of biofilms as compared to antibiotics. 17,[19][20][21][22][23][24] Ozone therapy for infections seems to have similarities with hyperbaric oxygen treatment. Animal studies comparing these 2 modalities in acute pancreas infection showed positive results for both treatments with a clear prevalence for ozone therapy.…”
Section: Discussionmentioning
confidence: 99%
“…17 Results on its activity on biofilms are not so univocal; however, ozone seems to have better destructive capacity than common treatment with antibiotics. [18][19][20][21][22][23][24] Toxicological tests indicated that ozone, when applied in acute and subacute doses, does not damage biological tissue. 25 This is a report on a case of resistant postoperative spine surgery infection treated successfully with the intrawound application of the gaseous form of ozone.…”
Section: Introductionmentioning
confidence: 99%
“…LULIN MA 1 , SONG WEN 1 , JIE YUAN 1,2 , DEXIN ZHANG 1 , YAN-LIU LU 3 , YOU ZHANG 4 , YING LI 1 and SONG CAO 1,2 oxidative and anti-pathogenic effects and immune regulation ability, as well as the increase of oxygen supply and reduction of oxidative stress (12,(20)(21)(22)(23)(24)(25)(26)(27). For instance, ozone was proven to relieve pain by causing the following effects: i) Release of endorphins (26); ii) inhibition of the activation of microglia via adenosine monophosphate (AMP)-dependent protein kinase signaling (28); iii) inhibition of the expression of purinergic receptors P2X3 and P2X7 in the spinal dorsal horn (29); iv) promoting phosphodiesterase 2A-cyclic guanosine monophosphate/cyclic AMP/NFκB-p65 signaling (30); v) inhibition of autophagy (31,32); vi) reduction of the expression of pro-inflammatory/pro-apoptotic caspases (33); and vii) increase of oxygen supply in tissues and cells (22).…”
Section: Detection Of Chlorite Chlorate and Perchlorate In Ozonated mentioning
confidence: 99%